Direito de arena - Zaparoli, Rodrigo Alves (2016)
The present dissertation aims to provide a full analysis concerning the Arena Rights, under the aspect of the Substantive Law, it will be initially addressed on the current context in which it is rooted in the legal institute debate, which presents itself as a species of image rights, this can be found on the personality rights list. Regarding the broad study of this subject, we will be guided by legislative, doctrinal, jurisprudential and field researches, with the purpose of showing the definition, the history evolution, the ownership, the legal nature, the application of exclusionary and major controversies surrounding the arena right, that emerges like a relevant subject and full of doctrinal and jurisprudential controversy. In the end of the mentioned approach, we dedicate ourselves to develop the comparative study of Portuguese and Spanish law, which are intended to control the marketing of images of the sporting spectacle, proposal that presents valuable to understand the subject in the international context